2019
DOI: 10.7771/2157-9288.1223
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Studies on Educational Robotics

Abstract: for additional information. This is an Open Access journal. This means that it uses a funding model that does not charge readers or their institutions for access. Readers may freely read, download, copy, distribute, print, search, or link to the full texts of articles. This journal is covered under the CC BY-NC-ND license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
16

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 277 publications
(163 citation statements)
references
References 124 publications
4
82
0
16
Order By: Relevance
“…While the amount of data was relatively small at that time, it was comparable to the amount of data collected in other traditional educational and psychological studies. Research on AI in education over the past few decades has been dedicated to advancing intelligent computing technologies such as intelligent tutoring systems (Graesser et al, 2005;Gobert et al, 2013;Nye, 2015), robotic systems (Toh et al, 2016;Anwar et al, 2019), and chatbots (Smutny and Schreiberova, 2020). With the breakthroughs in information technologies in the last decade, educational psychologists have had greater access to big data.…”
Section: Introductionmentioning
confidence: 99%
“…While the amount of data was relatively small at that time, it was comparable to the amount of data collected in other traditional educational and psychological studies. Research on AI in education over the past few decades has been dedicated to advancing intelligent computing technologies such as intelligent tutoring systems (Graesser et al, 2005;Gobert et al, 2013;Nye, 2015), robotic systems (Toh et al, 2016;Anwar et al, 2019), and chatbots (Smutny and Schreiberova, 2020). With the breakthroughs in information technologies in the last decade, educational psychologists have had greater access to big data.…”
Section: Introductionmentioning
confidence: 99%
“…The integration of educational robotics in educational settings has been noted both in and out of school environments to enhance K-12 students' engagement and academic achievement in various fields of STEAM [59] and non-STEAM education [60]. Many systematic reviews on educational robotics in diverse educational settings highlight their potential learning gains [61]. Benitti, in her systematic review [12], reported that the learning gains deriving from the use of robotics could be summarized into two categories: (i) the learning concepts/subjects and (ii) the development of skills.…”
Section: B Investigating the Expected Learning Outcomesmentioning
confidence: 99%
“…Em tempos em que a utilização de robôs é crescente nas mais diferentes áreas, a Educação, especificamente no sentido de ensino e aprendizagem, observou um crescente número de estudos que investigam a robótica educacional e seu impacto nas habilidades acadêmicas e sociais (ANWAR et al, 2019). Cabe destacar, que a robótica já integra o contexto educativo há muito tempo.…”
Section: Referencial Teóricounclassified